The Application to Find Cutting Patterns in Two Dimensional Cutting Stock Problem (Journal of Informatics and Mathematical Sciences, 2017)
Two dimensional Cutting Stock Problem (CSP) is a problem tofind the appropriate patterns that fulfilled the demand with different length and cut from two sides, the length and width. Two dimensional CSP aims to minimize the cutting waste that called Trim Loss. This research designed and made the application of finding cutting patterns in two dimensional CSP. Based on the results, it found that Modified Branch and Bound Algorithm makes the pattern searching become easier than manual searching. This application also yields the optimal patterns with minimum Trim Loss.
Keywords: Cutting Stock Problem; Trim Loss; Modified Branch and Bound Algorithm